2022
DOI: 10.1002/ecy.3862
|View full text |Cite
|
Sign up to set email alerts
|

Warming reduced flowering synchrony and extended community flowering season in an alpine meadow on the Tibetan Plateau

Abstract: The timing of phenological events is highly sensitive to climate change, and may influence ecosystem structure and function. Although changes in flowering phenology among species under climate change have been reported widely, how species-specific shifts will affect phenological synchrony and community-level phenology patterns remains unclear. We conducted a manipulative experiment of warming and precipitation addition and reduction to explore how climate change affected flowering phenology at the species and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 81 publications
0
21
0
Order By: Relevance
“…Thus, precipitation may not be the most important driver of plant reproductive phenology at the study site (Chen et al, 2023;Suonan et al, 2019). Moreover, Ganjurjav et al (2020) also found that early spring precipitation addition can offset the delaying effects of warming only in a dry year on the Tibetan Plateau, which was not the case in wet years.…”
Section: No Significant Phenological Response Of Alpine Plant Communi...mentioning
confidence: 93%
See 4 more Smart Citations
“…Thus, precipitation may not be the most important driver of plant reproductive phenology at the study site (Chen et al, 2023;Suonan et al, 2019). Moreover, Ganjurjav et al (2020) also found that early spring precipitation addition can offset the delaying effects of warming only in a dry year on the Tibetan Plateau, which was not the case in wet years.…”
Section: No Significant Phenological Response Of Alpine Plant Communi...mentioning
confidence: 93%
“…The other quadrat was used as a fixed quadrat to observe phenological events during the annual growing season (Figure S1). We monitored reproductive phenological traits every 6-7 days during the growing seasons (from late March to late October) of 2021 and 2022 (Chen et al, 2023;Sherry et al, 2007).…”
Section: Phenology Monitoringmentioning
confidence: 99%
See 3 more Smart Citations